Poor outcome after hematopoietic stem cell transplantation of patients with unclassified inherited bone marrow failure syndromes. (13th January 2022) - Lim, Yeon Jung; Arbiv, Omri A.; Kalbfleisch, Melanie E.; Klaassen, Robert J.; Fernandez, Conrad; Rayar, Meera; Steele, MacGregor; Lipton, Jeffrey H.; Cuvelier, Geoff; Pastore, Yves D.; Silva, Mariana; Brossard, Josee; et al.
Abstract: Classification of inherited bone marrow failure syndromes (IBMFSs) according to clinical and genetic diagnoses enables proper adjustment of treatment. Unfortunately, 30% of patients enrolled in the Canadian Inherited Marrow Failure Registry (CIMFR) with features suggesting hereditability could not be classified with a specific syndromic diagnosis. We analyzed the outcome of hematopoietic stem cell transplantation (HSCT) in unclassified IBMFSs (uIBMFSs) and the factors associated with outcome. Twenty‐two patients with uIBMFSs and 70 patients with classified IBMFSs underwent HSCT. Five‐year overall survival of uIBMFS patients after HSCT was inferior to that of patients with classified IBMFSs (56% vs 76.5%). The outcome of patients with uIBMFS who received cord blood was significantly lower than that of patients who received other stem cell sources (14.8% vs 90.9%). Engraftment failure was higher among patients with uIBMFS who received cord blood than those who received bone marrow. None of the following factors were significantly associated with poor survival: transfusion load, transplant indication, the intensity of conditioning regimen, human leukocyte antigen‐identical sibling/alternative donor. We suggest that identifying the genetic diagnosis is essential to modulate the transplant procedure including conditioning agents and stem cell sources for better outcome and the standard cord blood transplantation (CBT) should be avoided in uIBMFS.